Factors associated with nurse assistance among peritoneal dialysis patients: a cohort study from the French Language Peritoneal Dialysis Registry. Issue 8 (25th December 2017) - Guillouët, Sonia; Lobbedez, Thierry; Lanot, Antoine; Verger, Christian; Ficheux, Maxence; Béchade, Clémence
Abstract: Background: No information is available regarding nurse-assisted peritoneal dialysis (PD) in non-elderly subjects. This study was carried out to estimate the rate of nurse-assisted PD among non-elderly patients and to assess which individual and centre factors were associated with nurse-assisted PD. The other objective was to estimate the magnitude of the centre effect on the utilization of nurse-assisted PD using hierarchical modelling. Methods: This was a retrospective study based on data from the French Language Peritoneal Dialysis Registry. Patients incident on PD > 18 and < 65 years of age were included. Results: There were 2269 incidents of PD initiation between January 2008 and December 2012 in 127 PD centres with 114 (5%) on family-assisted PD and 272 (12%) on nurse-assisted PD. At the individual level, compared with autonomous patients, nurse assistance was associated with age odds ratio [OR] 1.79 [95% confidence interval (CI) 1.51–2.13], gender [OR 0.47 (95% CI 0.35–0.64)], comorbidities and underlying nephropathy. There was significant heterogeneity between centres in the nurse assistance utilization (variance of random effect 0.12). At the centre level, the type of centre, centre experience, centre organization and private nurse density were not associated with nurse-assisted PD. Conclusions: The rate of nurse-assisted PD among non-elderly patients was 12%. There was a significant centre effect in the utilization of nurse assistance that was not explained by the centres' characteristics. Nurse-assisted PD utilization in non-elderly patients is associated with patient characteristics and also with centre practices.